2020
DOI: 10.1149/1945-7111/ab6b05
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fabrication of Porous Nanostructures Derived from Bimetal-Organic Frameworks for Highly Sensitive Non-Enzymatic Glucose Sensors

Abstract: Metal-organic framework (MOF) based porous derivatives have been attractive materials for high-performance electrochemical sensors due to their high surface-area, stability and activities. Herein, an in situ fabrication method is proposed to obtain porous Cu/Co bimetallic MOF-based derivatives on the flexible carbon cloth for glucose sensing. The process is also developed with three critical steps. Firstly, uniform Cu(OH)2 nanorods are directly formed through wet chemical method on Cu sputtered carbon cloth. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…It is pivotal to note that a majority of these groundbreaking MOF-centric sensors have undergone rigorous testing across varied body fluids, notably blood serum, urine, and saliva. 126 In a recent study, Wang et al heralded a significant leap in sweat sensing methodologies. Given the pocket composed by tryptophan (Trp)/histidine (His) and copper sites, natural ascorbate oxidase can selectively captured and identified ascorbate (Fig.…”
Section: Case Studies Of Notable Wearable Electrochemical Sensors Uti...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is pivotal to note that a majority of these groundbreaking MOF-centric sensors have undergone rigorous testing across varied body fluids, notably blood serum, urine, and saliva. 126 In a recent study, Wang et al heralded a significant leap in sweat sensing methodologies. Given the pocket composed by tryptophan (Trp)/histidine (His) and copper sites, natural ascorbate oxidase can selectively captured and identified ascorbate (Fig.…”
Section: Case Studies Of Notable Wearable Electrochemical Sensors Uti...mentioning
confidence: 99%
“…5C–G), 119 Cu–CAT MOF fractals on carbon paper, 125 and the bimetallic 2D Cu–Co–ZIF derivatives on CC. 126 A standout iteration in this series is the bimetallic 2D Cu–Co–ZIF derivative on a flexible CC electrode. Its superlative sensitivity, eclipsing other MOFs and MOF-derived materials, is credited to its distinct 2D blueprint and the synergetic redox dynamism of Cu and Co ions in alkaline surroundings.…”
Section: Artificial Enzymes In Wearable Electrochemical Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other researchers developed flexible and enzymeless electrochemical detection systems of glucose, based on a variety of MOFs composites, including CuO/NiO/carbon nanocomposites deposited on cello tape, [ 113 ] sandpaper‐supported Cu‐MOF, [ 194 ] Co‐MOF/CC/paper, [ 195 ] ZIF‐67/carbon fibers, [ 196 ] Cu‐catecholate (Cu‐CAT) MOF fractals/carbon paper, [ 197 ] and Cu‐Co‐ZIF derivatives/CC. [ 198 ] The analytical performances of these sensors are summarized in Table 6 , which indicated that the bimetallic 2D Cu‐Co‐ZIF derivative modified flexible CC electrode showed remarkably high sensitivity compared to the reported other pristine MOFs, MOF composites, and MOF‐derived materials, [ 198 ] conceivably due to the enriched reaction sites induced by the 2D structures as well as the synergistic effect of Cu 1+/2+ and Co 2+/3+ redox pairs formed in an alkaline medium for the mediated oxidation of glucose. Most of these flexible MOFs‐based sensors were, however, applied to more common body fluids such as human blood serum, urine, saliva.…”
Section: Mof‐based Wearable and Flexible Glucose Sensorsmentioning
confidence: 99%
“…34 Besides, compared with monometallic MOFs, bimetallic MOFs have synergistic effects and strong electronic effects between the two metals, it can improve the sensing performance of MOFs materials. 35,36 Also,it is reported that Ni/ Co bimetallic MOFs have good catalytic properties for glucose in lye. Li and his colleagues report that two-dimensional Ni/Co bimetallic MOFs nanosheets are used in glucose sensors.…”
mentioning
confidence: 99%